Generalized Extended Tanh-Function Method for Traveling Wave Solutions of Nonlinear Physical Equations (Communications in Mathematical Research, 2021)
In this paper, the generalized extended tanh-function method is used forconstructing the traveling wave solutions of nonlinear evolution equations. We chooseFisher's equation, the nonlinear schrödinger equation to illustrate the validity and advantages of the method. Many new and more general traveling wave solutions areobtained. Furthermore, this method can also be applied to other nonlinear equationsin physics.
Keywords: generalized tanh-function method; nonlinear Schrödinger equation; Fisher's equation.